Maize Production and Soil Properties Change in Alley Cropping System at Different Nitrogen Levels - Rahman, Md Abiar; Miah, Md Giashuddin; Yahata, Hisashi (The Agriculturists, 2010)
Productivity of maize and soil properties change under alley cropping system consisting of four woody species (Gliricidia sepium, Leucaena leucocephala, Cajanus cajan and Senna siamea) at different nitrogen levels (0, 25, 50, 75 and 100% of recommended rate) were studied in the floodplain ecosystem of Bangladesh. Comparative growth performance of four woody species after pruning showed that L. leucocephala attained the highest height, while C. cajan produced the maximum number of branches. Higher and almost similar amount of pruned materials (PM) were obtained from S. siamea, G. sepium and C. cajan species. In general, maize yield increased with the increase in N level irrespective of added PM. However, 100% N plus PM, 75% N plus PM and 100% N without PM (control) produced similar yields. The grain yield of maize obtained from G. sepium alley was 2.82, 4.13 and 5.81% higher over those of L. leucocephala, C. cajan and S. siamea, respectively. Across the alley, only one row of maize in the vicinity of the woody species was affected significantly. There was an increasing trend in soil properties in terms of organic C, total N and CEC in alley cropping treatments especially in G. sepium and L. leucocephala alleys compared to the initial and control soils. Therefore, one fourth chemical N fertilizer can be saved without significant yield loss in maize production in alley cropping system.